Applications of electrospinning for fuel cell and electrolysis cell applications in hydrogen technologies - Antara Sarkar; Jerome Michael Bidu; Jagannath Panda; Young Je Kwon; Sohwi Bak; Kie Yong Cho; Segi Byun; Jun Young Cheong (Energy Reviews)
With the diminishing reserves of fossil fuels and their detrimental environmental impacts, there has been a significant drive towards exploring alternative renewable energy sources. Among these, hydrogen emerges as a promising clean energy carrier, offering a viable alternative to traditional fossil fuels. Both the fuel cell and electrolysis cell capable of utilizing green hydrogen with the aid of electrospinning methods have attracted considerable attention for improving the hydrogen production or utilization efficiency and operational stability. This comprehensive review elucidates the fundamental principles of electrospinning and its applications in fabricating proton exchange membranes and solid oxide electrolysis/fuel-cells (PEMFC/ECs and SOFC/EC). With a primary focus on current status and future perspectives on employing electrospinning techniques for fuel cell and electrolysis cell in hydrogen technology, this review provides insights and knowledge relevant to applying electrospinning for hydrogen technologies.